If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 28 = 27x + 2 Reorder the terms: 28 + 7x = 27x + 2 Reorder the terms: 28 + 7x = 2 + 27x Solving 28 + 7x = 2 + 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. 28 + 7x + -27x = 2 + 27x + -27x Combine like terms: 7x + -27x = -20x 28 + -20x = 2 + 27x + -27x Combine like terms: 27x + -27x = 0 28 + -20x = 2 + 0 28 + -20x = 2 Add '-28' to each side of the equation. 28 + -28 + -20x = 2 + -28 Combine like terms: 28 + -28 = 0 0 + -20x = 2 + -28 -20x = 2 + -28 Combine like terms: 2 + -28 = -26 -20x = -26 Divide each side by '-20'. x = 1.3 Simplifying x = 1.3
| 36x^2-169y^2= | | p-36=-48 | | x^2+3x^2=40 | | -2x-7=13x-5 | | 7-6[9-(4y-3)]= | | 4x+36=12x-32 | | (4x+4)*(7x-3)= | | (4x+4)(7x-3)= | | 18x+16=60 | | 3x=7x-12-5x | | 2(4+x)=18 | | 15x+4*4=18x*3 | | 15x+4*4=3*18x | | -2x-9-4x=9x+21 | | 6(3+4x)=282 | | 5x^2-23x-42=0 | | 15x+4*x=21 | | y^3+10y^2+24y=0 | | x+4+3x=12 | | 2y+6=y+10 | | y^2-9y=-14 | | 2n-7+3n=18 | | 2x+6+6x=86 | | t^2-2t=20 | | 27x^2-18x+3=0 | | 10x^2+72x-64=0 | | 102-(4x+15)=4(x+6)+x | | y^2(y-4)=5y-14 | | 48-16= | | x^2+6x+13=x+5 | | 18-2g=4 | | S=-16t^2+48t |